Why we need a common curriculum in veterinary public health - Vilhena, Manuela (2012)
In this paper we present some of the results achieved by the “THE SAPUVETNET III PROJECT Contributing to Millennium Development Goals through the One Health Concept”, EU_ALFA n. DCI-ALA/19.09.01/08/19189/169-157/ALFA III-75. With the curriculum and manual we intend to bridge gaps of knowledge in veterinary public health institutions in Latin America and Europe. The implementation of a common curriculum will enhance possibilities to collaborate in research and surveillance between institutions from both continents. In addition to this direct consequence in education, the achievement of a common language will promote transparency in global trade and a better collaboration and cooperation in global sanitation and consequently more food security and food safety. Here we present also a new journal, the one health/Uma Saúde/Una Salud, an instrument of teaching as well as of dissemination of knowledge.